ANALYSIS PERSONALITY OF ARCHETYPE IN THE MAIN CHARACTER OF ADELAIDE IN THE MOVIE "US " - Iyohu, Indri Yani; Balango, Mery; Podungge, Rusni (VARIABLE RESEARCH JOURNAL, 2024)
In this study, Jordan Peele's film Us is analyzed using the analytical descriptive method of Jungian studies. This study aims to analyze the archetypal personality of the main character, Adelaide, in the film Us (2019) written and directed by Jordan Peele. The analysis uses Carl Gustav Jung's concept of archetypes, namely persona, shadow, animus, and great mother. Persona represents the social face Adelaide displays as a gentle and protective mother figure in everyday life. Shadow emerges through Adelaide's hidden character, namely the figure of 'Red' who reveals her dark side and hidden trauma. The animus element is seen in Adelaide's strength and courage as she protects her family, showing the hidden masculine aspect of herself. The great mother archetype comes into play through Adelaide's role as a protector, where she shows not only deep maternal love but also destructive power when facing threats. The conclusion of this study shows that the character of Adelaide in Us depicts the complexity of human personality through the encounter between Jungian archetypes, which shows the inner dynamics of human beings between light and darkness, strength and tenderness, and trauma and healing.